A method for preparing high-gloss glazed ceramic tile

Through a method that combines ball milling, spray drying and high-temperature sintering, the problem of insufficient gloss of high-gloss glazed tiles in the existing technology is solved, and the gloss of the tiles is significantly improved and multiple properties are improved.

CN117902877BActive Publication Date: 2025-01-21ZIBO HUAYUE BUILDING CERAMIC CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410086427.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-22
Publication Date
2025-01-21
Estimated Expiration
2044-01-22

AI Technical Summary

Technical Problem

The existing ceramic tile preparation technology has the problem of insufficient gloss in the preparation of high-gloss glazed ceramic tile, and it is difficult to take into account both efficiency and product quality.

Method used

A method for preparing high-gloss glazed ceramic tiles is adopted, which includes mixing and ball-milling sodium silicate, zinc oxide, calcium carbonate, kaolin and feldspar powder, adding an organic binder and spray-drying, followed by pressing and molding under a predetermined pressure, and finally Ceramic tiles that are fired at high temperatures to create a high-gloss glaze.

Benefits of technology

It significantly improves the gloss of ceramic tiles, ensures even distribution and full melting of the glaze layer, enhances the wear resistance, durability and chemical stability of ceramic tiles, while improving production efficiency and cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117902877B_ABST
    Figure CN117902877B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of ceramic material preparation, and in particular to a method for preparing high-gloss glazed ceramic tiles, comprising the following steps: S1: mixing sodium silicate, zinc oxide, calcium carbonate, kaolin, and feldspar powder according to a preset weight ratio to form a mixed raw material; S2: ball-milling the mixed raw material of S1 in a ball mill to form a slurry; S3: adding an organic binder to the ball-milled slurry and mixing; S4: spray-drying the slurry with the organic binder; S5: pressing and molding the dry powder obtained in step S4 under a predetermined pressure; S6: uniformly applying a layer of high-gloss glaze on the ceramic tile blank; S7: subjecting the glazed ceramic tile to a high-temperature sintering treatment. The present invention not only significantly improves the glossiness and aesthetics of the ceramic tile, but also enhances the physical and chemical stability of the ceramic tile through an optimized preparation process, and also achieves remarkable results in improving production efficiency and economy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic material preparation, and in particular to a method for preparing high-gloss glazed ceramic tiles. Background Art

[0002] As a widely used building decoration material, the beauty, durability and practicality of ceramic tiles are crucial to modern architectural design, especially in the field of high-end decoration. The glossiness of ceramic tiles has become one of the important criteria for measuring their quality. Although traditional ceramic tile preparation technology can produce a variety of ceramic tile products, there are still some limitations in the preparation of high-gloss glazed ceramic tiles. The problem of insufficient gloss often plagues manufacturers, especially in occasions that require high-end decorative effects.

[0003] One of the main challenges facing existing tile preparation technology is how to effectively improve the gloss of tiles while maintaining their physical and chemical properties to adapt to different usage environments and decorative requirements. In addition, existing methods often find it difficult to balance efficiency and product quality in terms of tile body preparation, glaze formulation, and sintering processes. For example, during the preparation and application of glazes, traditional methods may not be able to evenly apply or completely melt the glaze, resulting in uneven gloss of the finished tiles. At the same time, temperature control and body densification during sintering are also key factors affecting the final gloss.

[0004] Therefore, there is an urgent need for an improved ceramic tile preparation method that can effectively solve the above-mentioned problems, improve the glossiness of the ceramic tiles, and at the same time ensure their durability and applicability to meet the market demand for high-quality ceramic tiles. Summary of the invention

[0005] Based on the above purpose, the present invention provides a method for preparing high-gloss glazed ceramic tiles.

[0006] A method for preparing high-gloss glazed ceramic tiles comprises the following steps:

[0007] S1: Mixing sodium silicate, zinc oxide, calcium carbonate, kaolin, and feldspar powder according to a preset weight ratio to form a mixed raw material;

[0008] S2: ball milling the mixed raw materials of S1 in a ball mill to form a slurry;

[0009] S3: adding an organic binder to the ball-milled slurry and mixing;

[0010] S4: spray drying the slurry to which the organic binder is added to form a dry powder;

[0011] S5: Pressing the dry powder obtained in step S4 under a predetermined pressure to form a ceramic tile body;

[0012] S6: Apply a layer of high gloss glaze evenly on the tile body;

[0013] S7: The glazed tiles are subjected to high temperature sintering treatment, and after cooling, a high-gloss glazed tile product is obtained.

[0014] Furthermore, the preset weight ratio in S1 is specifically 17-35% of sodium silicate, 5-8% of zinc oxide, 20-25% of calcium carbonate, 25-30% of kaolin, and 15-20% of feldspar powder.

[0015] Furthermore, the components of the high-gloss glaze in S6 include 18% zirconium silicate, 12% aluminum oxide, 7% boric acid, 13% sodium silicate, 7% titanium dioxide, 3% titanium oxide, 5% strontium oxide, 13% feldspar, 3% barium carbonate and 19% additives, and the additives are lithium oxide, potassium oxide or sodium oxide.

[0016] Furthermore, the S2 specifically includes:

[0017] S21: firstly putting the mixed raw materials in S1 into a ball mill, and then adding water into the ball mill to form an initial slurry, and controlling the weight ratio of the mixed raw materials to water to be 1:0.6 to 1:1.2;

[0018] S22: ball milling the initial slurry in a ball mill, wherein the ball milling time is within 4-8 hours and the rotation speed of the ball mill is controlled at 60-120 rpm;

[0019] S23: After the ball milling is completed, the slurry is filtered using a filter screen with a pore size of 0.5 microns to screen out the slurry with a particle size less than 0.5 microns for use.

[0020] Furthermore, the S3 specifically includes:

[0021] S31: the selected organic binder is polyvinyl alcohol, methyl cellulose or carboxymethyl cellulose;

[0022] S32: accurately weighing the selected organic binder at a ratio of 0.5-2% of the weight of the slurry;

[0023] S33: adding the weighed organic binder to the ball-milled slurry, stirring and mixing at a speed of 60-80 rpm for 15-30 minutes;

[0024] S34: During the entire mixing process, the temperature of the slurry is maintained at 20-35°C;

[0025] S35: After the mixing is completed, the viscosity of the slurry is checked and controlled at 600-1200 mPa·s.

[0026] Furthermore, the S4 specifically includes:

[0027] S41: transferring the slurry containing the organic binder to a spray drying device;

[0028] S42: During the spray drying process, the nozzle pressure is controlled to be 2-5 bar, and the inlet temperature of the spray drying chamber is set to be 150-200° C. and the outlet temperature is set to be 70-100° C.;

[0029] S43: After drying is completed, the moisture content of the collected dry powder is controlled to be less than 0.5%.

[0030] Furthermore, the S5 specifically includes:

[0031] S51: filling the dry powder obtained in S4 evenly into a pressing mold;

[0032] S52: During the pressing process, the pressure of the press is set to 2000-5000 tons, and the pressing time is controlled to 30-60 seconds;

[0033] S53: After the pressing is completed, the pressure is slowly unloaded, and the ceramic tile body is taken out of the mold at room temperature to obtain the ceramic tile body.

[0034] Furthermore, the preparation steps of the high gloss glaze in S6 are as follows:

[0035] S61: Mixing zirconium silicate, aluminum oxide, boric acid, sodium silicate, titanium dioxide, titanium oxide, strontium oxide, feldspar, barium carbonate and additives according to a preset ratio to prepare a glaze powder;

[0036] S62: mixing the prepared glaze powder with water in a weight ratio of 1:0.5 to 1:1 to form a glaze slurry;

[0037] S63: Use a filter with a pore size of 0.3 to 0.5 microns to filter the glaze slurry to remove large particles or impurities;

[0038] S64: Use a spray gun or glaze dipping machine to evenly apply the glaze slurry on the surface of the tile body, and control the glazing thickness to 0.2-0.5 mm;

[0039] S65: The glazed ceramic tile is allowed to dry naturally at room temperature until the surface of the glaze layer is dry and there is no obvious sign of moisture.

[0040] Furthermore, the S7 specifically includes:

[0041] S71: placing the glazed ceramic tile body in a sintering kiln, and setting the initial temperature of the sintering kiln to room temperature;

[0042] S72: gradually increasing the temperature of the sintering kiln at a rate of 100° C. per hour until the sintering temperature reaches 1250-1350° C.;

[0043] S73: Maintain at the sintering temperature of S72 for 1-2 hours;

[0044] S74: After the sintering process is completed, the sintering kiln temperature is gradually reduced, still at a cooling rate of 100° C. per hour;

[0045] S75: After the temperature of the ceramic tile drops to room temperature, the ceramic tile is taken out from the sintering kiln to obtain the final ceramic tile product with high gloss glaze.

[0046] Beneficial effects of the present invention:

[0047] The present invention, by adopting high-gloss glaze in combination with effective glazing technology, significantly improves the surface gloss of the tile, ensures the uniform distribution and full melting of the glaze layer, thereby giving the tile higher gloss and more attractive visual effects. This improvement is of great significance for improving the aesthetics and market competitiveness of the tile.

[0048] The present invention effectively improves the density and uniformity of the ceramic tile through the fine processing of the raw materials and the pressing and forming process of the green body, thereby enhancing its wear resistance and durability. In addition, the optimized high-temperature sintering process further ensures the chemical stability and structural integrity of the ceramic tile, making it more suitable for long-term use.

[0049] The present invention not only improves production efficiency but also reduces waste of raw materials by optimizing the preparation process, such as efficient spray drying and precise pressing and molding. These improvements enable the ceramic tile preparation method of the present invention to have high cost-effectiveness while ensuring product quality, which is conducive to gaining an advantage in a fiercely competitive market. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0051] Figure 1 The present invention is a schematic diagram of a method for preparing high-gloss glazed ceramic tiles according to an embodiment of the present invention. DETAILED DESCRIPTION

[0052] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0053] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should be understood by people with ordinary skills in the field to which the present invention belongs. The "first", "second" and similar words used in the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. "Include" or "comprise" and similar words mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. "Connect" or "connected" and similar words are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.

[0054] Example 1

[0055] like Figure 1 As shown, a method for preparing high-gloss glazed tiles comprises the following steps:

[0056] S1: Mixing sodium silicate, zinc oxide, calcium carbonate, kaolin, and feldspar powder according to a preset weight ratio to form a mixed raw material;

[0057] S2: ball milling the mixed raw materials of S1 in a ball mill to form a slurry to improve the density and uniformity of the tile body;

[0058] S3: adding an organic binder to the ball-milled slurry and mixing it to improve the adhesion and strength of the tile body before molding;

[0059] S4: spray drying the slurry to which the organic binder is added to form a dry powder;

[0060] S5: Pressing the dry powder obtained in step S4 under a predetermined pressure to form a ceramic tile body;

[0061] S6: Apply a layer of high gloss glaze evenly on the tile body;

[0062] S7: The glazed tiles are subjected to high temperature sintering treatment, and after cooling, a high-gloss glazed tile product is obtained.

[0063] The preset weight ratios in S1 are specifically 27% sodium silicate, 6% zinc oxide, 22% calcium carbonate, 27% kaolin, and 18% feldspar powder.

[0064] The components of the high-gloss glaze in S6 include 18% zirconium silicate, 12% aluminum oxide, 7% boric acid, 13% sodium silicate, 7% titanium dioxide, 3% titanium oxide, 5% strontium oxide, 13% feldspar, 3% barium carbonate and 19% additives, the additive being lithium oxide.

[0065] S2 specifically includes:

[0066] S21: firstly put the mixed raw materials in S1 into a ball mill, and then add water into the ball mill to form an initial slurry, and control the weight ratio of the mixed raw materials to water to be 1:0.9;

[0067] S22: ball milling the initial slurry in a ball mill, wherein the ball milling time is within 6 hours and the speed of the ball mill is controlled to be 80 revolutions per minute to optimize the ball milling effect and prevent over-grinding of the raw material;

[0068] S23: After the ball milling is completed, the slurry is filtered through a filter with a pore size of 0.5 microns to select the slurry with a particle size less than 0.5 microns for use, ensuring the fineness and uniformity of the slurry.

[0069] S3 specifically includes:

[0070] S31: the selected organic binder is polyvinyl alcohol;

[0071] S32: accurately weighing the selected organic binder at a ratio of 1% of the weight of the slurry;

[0072] S33: adding the weighed organic binder to the ball-milled slurry, stirring and mixing at a rotation speed of 70 rpm for 25 minutes;

[0073] S34: During the entire mixing process, the temperature of the slurry is maintained at 30°C to ensure uniform dispersion and effective action of the organic binder;

[0074] S35: After the mixing is completed, the viscosity of the slurry is checked and controlled at 900 mPa·s to facilitate the subsequent spray drying process.

[0075] S4 specifically includes:

[0076] S41: transferring the slurry containing the organic binder to a spray drying device;

[0077] S42: During the spray drying process, the nozzle pressure is controlled to be 3 bar, and the inlet temperature of the spray drying chamber is set to 175°C and the outlet temperature is set to 85°C to ensure effective drying of the slurry without destroying the structure of the organic binder;

[0078] S43: After drying, the moisture content of the collected dry powder is controlled to be 0.3% to facilitate subsequent pressing and molding process.

[0079] S5 specifically includes:

[0080] S51: filling the dry powder obtained in S4 evenly into a pressing mold;

[0081] S52: During the pressing process, the pressure of the press was set to 3000 tons and the pressing time was controlled to 45 seconds to prevent cracks or deformation caused by excessive compaction;

[0082] S53: After the pressing is completed, the pressure is slowly unloaded, and the ceramic tile body is taken out of the mold at room temperature to obtain the ceramic tile body.

[0083] The preparation steps of S6 medium-high gloss glaze are:

[0084] S61: Mixing zirconium silicate, aluminum oxide, boric acid, sodium silicate, titanium dioxide, titanium oxide, strontium oxide, feldspar, barium carbonate and additives according to a preset ratio to prepare a glaze powder;

[0085] S62: mixing the prepared glaze powder and water in a weight ratio of 1:0.7 to form a glaze slurry;

[0086] S63: Use a filter with a pore size of 0.4 microns to filter the glaze slurry to remove large particles or impurities to ensure the uniformity and smoothness of the glaze slurry;

[0087] S64: Use a spray gun to evenly apply the glaze slurry on the surface of the tile body, and control the glaze thickness to 0.4 mm;

[0088] S65: The glazed ceramic tile is allowed to dry naturally at room temperature until the surface of the glaze layer is dry and there is no obvious sign of moisture.

[0089] S7 specifically includes:

[0090] S71: placing the glazed ceramic tile body in a sintering kiln, and setting the initial temperature of the sintering kiln to room temperature;

[0091] S72: gradually increasing the temperature of the sintering kiln at a rate of 100° C. per hour until the sintering temperature reaches 1300° C.;

[0092] S73: Maintain the sintering temperature of S72 for 1.5 hours to ensure the full melting of the glaze and the densification of the tile body;

[0093] S74: After the sintering process is completed, the sintering kiln temperature is gradually reduced, still cooling at a rate of 100°C per hour to prevent thermal stress and cracking of the tiles due to rapid cooling;

[0094] S75: After the temperature of the ceramic tile drops to room temperature, the ceramic tile is taken out from the sintering kiln to obtain the final ceramic tile product with high gloss glaze.

[0095] Example 2

[0096] S1: Raw material mixing, firstly, the raw materials are mixed according to a preset ratio, wherein sodium silicate accounts for 35%, zinc oxide accounts for 5%, calcium carbonate accounts for 20%, kaolin accounts for 25%, and feldspar powder accounts for 15%, to form a mixed raw material;

[0097] S2: ball milling treatment, the mixed raw material and water are placed in a ball mill at a weight ratio of 1:0.6, the ball milling time is set to 4 hours, the speed is 120 rpm, and after the ball milling is completed, the slurry is filtered using a filter with a pore size of 0.5 microns to screen out the slurry with a particle size less than 0.5 microns for use;

[0098] S3: adding an organic binder, adding methyl cellulose as an organic binder to the ball-milled slurry in an amount of 0.5% of the slurry weight, stirring and mixing at a speed of 60 rpm for 15 minutes, ensuring that the slurry temperature is maintained at 20°C and the viscosity is controlled at 600 mPa·s;

[0099] S4: spray drying, treating the slurry containing the organic binder in a spray drying device, setting the nozzle pressure to 2 bar, the inlet temperature to 150°C, the outlet temperature to 70°C, and the moisture content of the dried powder to 0.4%;

[0100] S5: Pressing and molding, using the dried powder to press at a predetermined pressure, the pressure of the press is set to 2000 tons, the pressing time is 30 seconds, and then the pressure is slowly unloaded at room temperature, and the tile body is taken out;

[0101] S6: evenly apply high gloss glaze on the ceramic tile body, the glaze composition includes 18% zirconium silicate, 12% aluminum oxide, 7% boric acid, 13% sodium silicate, 7% titanium dioxide, 3% titanium oxide, 5% strontium oxide, 13% feldspar, 3% barium carbonate and 19% additive (lithium oxide), the glaze powder is mixed with water in a weight ratio of 1:0.5 to form a glaze slurry, and then the glaze slurry is filtered through a filter with a pore size of 0.3 microns to remove large particles or impurities, and then the glaze slurry is evenly applied to the surface of the ceramic tile body using a glazing machine, and the glazing thickness is controlled to be 0.2 mm;

[0102] S7: High temperature sintering. The glazed ceramic tile body is sintered in a sintering kiln. The initial temperature starts from room temperature and is increased to 1250°C at a rate of 100°C per hour. It is maintained at this temperature for 1 hour, and then gradually cooled down. The ceramic tile is taken out after the temperature drops to room temperature to obtain the final high-gloss glazed ceramic tile product.

[0103] Example 3

[0104] S1: Raw material mixing, firstly, the raw materials are mixed according to a preset ratio, wherein sodium silicate accounts for 17%, zinc oxide accounts for 8%, calcium carbonate accounts for 25%, kaolin accounts for 30%, and feldspar powder accounts for 20% to form a mixed raw material;

[0105] S2: ball milling treatment, the mixed raw materials and water are placed in a ball mill at a weight ratio of 1:1.2, the ball milling time is set to 8 hours, the speed is 60 rpm, and after the ball milling is completed, the slurry is filtered using a filter with a pore size of 0.5 microns to screen out the slurry with a particle size less than 0.5 microns for use;

[0106] S3: adding an organic binder, adding carboxymethyl cellulose as an organic binder to the ball-milled slurry in an amount of 2% of the slurry weight, stirring and mixing at a speed of 80 rpm for 30 minutes, ensuring that the slurry temperature is maintained at 35°C and the viscosity is controlled at 1200 mPa·s;

[0107] S4: spray drying, treating the slurry containing the organic binder in a spray drying device, setting the nozzle pressure to 5 bar, the inlet temperature to 200°C, the outlet temperature to 100°C, and the moisture content of the dried powder to 0.5%;

[0108] S5: Pressing and molding, using the dried powder to press at a predetermined pressure, the pressure of the press is set to 5000 tons, the pressing time is 60 seconds, and then the pressure is slowly unloaded at room temperature, and the tile body is taken out;

[0109] S6: evenly apply high gloss glaze on the ceramic tile body, the glaze composition includes 18% zirconium silicate, 12% aluminum oxide, 7% boric acid, 13% sodium silicate, 7% titanium dioxide, 3% titanium oxide, 5% strontium oxide, 13% feldspar, 3% barium carbonate and 19% additive (lithium oxide), the glaze powder is mixed with water in a weight ratio of 1:1.1 to form a glaze slurry, and then the glaze slurry is filtered through a filter with a pore size of 0.5 microns to remove large particles or impurities, and then the glaze slurry is evenly applied to the surface of the ceramic tile body using a spray gun, and the glaze thickness is controlled to be 0.5 mm;

[0110] S7: High temperature sintering. The glazed ceramic tile body is sintered in a sintering kiln. The initial temperature starts from room temperature and is increased to 1350°C at a rate of 100°C per hour. It is maintained at this temperature for 2 hours, and then gradually cooled down. The ceramic tile is taken out after the temperature drops to room temperature to obtain the final high-gloss glazed ceramic tile product.

[0111] Table 1 Comparison of performance data of finished high gloss glazed tiles

[0112] Performance Indicators Example 1 Example 2 Example 3 Glossiness (GU) 95 90 87 Breaking strength(MPa) 40 35 32 Water absorption (%) 0.1 0.3 0.5 Wear resistance (rotation) 15000 12000 10000 Thermal shock stability (number of times) 250 200 150

[0113] It can be seen from Table 1 above that the tiles of Example 1 show the highest glossiness (95GU), which indicates that its surface is smoother and more reflective, providing users with a brighter and clearer visual effect; the tiles of Example 1 have the highest breaking strength (40MPa), indicating that its material is stronger, has a stronger bearing capacity, and is more suitable for high-load environments; the tiles of Example 1 have the lowest water absorption rate (0.1%), which means that they are more resistant to moisture, reducing the risk of tile expansion or cracking due to water absorption, and are suitable for more humid environments; the tiles of Example 1 have a wear-resistant revolution number of up to 15,000, showing excellent wear resistance, which makes them more suitable for use in high-traffic areas, such as public places or commercial areas; the tiles of Example 1 can withstand more thermal shock cycles, have better temperature adaptability and stability, and are suitable for environments with large temperature differences.

[0114] Table 2 Comparison of other performance data of high gloss glazed ceramic tile finished products

[0115] Performance Indicators Example 1 Example 2 Example 3 Thermal expansion coefficient (×10^-6 / ℃) 6.5 7.2 7.8 Chemical resistance (grade) 1 2 3 Bending strength(MPa) 55 45 40 Impact resistance(cm) 80 70 65 Color consistency (grade) 1 2 3

[0116] It can be seen from Table 2 above that the ceramic tile of Example 1 has a lower coefficient of thermal expansion, indicating that it has better dimensional stability under temperature changes and is suitable for environments with large temperature differences; the ceramic tile of Example 1 has the highest chemical resistance (grade 1), indicating that its surface has stronger resistance to chemicals such as detergents, acids, alkalis, etc., and is suitable for environments that require frequent cleaning or chemical exposure; the ceramic tile of Example 1 shows higher flexural strength (55MPa), which means that it is not easy to break under heavy pressure or structural bending; the ceramic tile of Example 1 has higher impact resistance (80cm), is not easily damaged when subjected to physical impact, and is suitable for areas with high frequency use or prone to collision; the ceramic tile of Example 1 reaches the highest grade in color consistency, indicating that its surface color is uniform and consistent, and its appearance is more beautiful.

[0117] In summary, the high-gloss glazed ceramic tile of Example 1 is superior to that of Examples 2 and 3 in multiple performance indicators, showing better comprehensive performance, and is a more excellent ceramic tile choice.

[0118] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing high-gloss glazed tiles, characterized in that: The following steps are involved: S1: Mixing sodium silicate, zinc oxide, calcium carbonate, kaolin, and feldspar powder according to a preset weight ratio to form a mixed raw material; S2: ball milling the mixed raw materials of S1 in a ball mill to form a slurry; S3: adding an organic binder to the ball-milled slurry and mixing; The S3 specifically includes: S31: the selected organic binder is polyvinyl alcohol, methyl cellulose or carboxymethyl cellulose; S32: accurately weighing the selected organic binder at a ratio of 0.5-2% of the weight of the slurry; S33: adding the weighed organic binder to the ball-milled slurry, stirring and mixing at a speed of 60-80 rpm for 15-30 minutes; S34: During the entire mixing process, the temperature of the slurry is maintained at 20-35°C; S35: After the mixing is completed, the viscosity of the slurry is checked and controlled at 600-1200 mPa·s; S4: spray drying the slurry to which the organic binder is added to form a dry powder; S5: Pressing the dry powder obtained in step S4 under a predetermined pressure to form a ceramic tile body; S6: Apply a layer of high gloss glaze evenly on the tile body; The components of the high gloss glaze in S6 include 18% zirconium silicate, 12% aluminum oxide, 7% boric acid, 13% sodium silicate, 7% titanium dioxide, 3% titanium oxide, 5% strontium oxide, 13% feldspar, 3% barium carbonate and 19% additives, wherein the additives are lithium oxide, potassium oxide or sodium oxide; The preparation steps of the S6 medium-high gloss glaze are as follows: S61: Mixing zirconium silicate, aluminum oxide, boric acid, sodium silicate, titanium dioxide, titanium oxide, strontium oxide, feldspar, barium carbonate and additives according to a preset ratio to prepare a glaze powder; S62: mixing the prepared glaze powder with water in a weight ratio of 1:0.5 to 1:1 to form a glaze slurry; S63: Use a filter with a pore size of 0.3 to 0.5 microns to filter the glaze slurry to remove large particles or impurities; S64: Use a spray gun or glaze dipping machine to evenly apply the glaze slurry on the surface of the tile body, and control the glazing thickness to 0.2-0.5 mm; S65: The glazed ceramic tile is allowed to dry naturally at room temperature until the glaze surface is dry and there is no obvious trace of moisture; S7: The glazed tiles are subjected to high temperature sintering treatment, and after cooling, a high-gloss glazed tile product is obtained.

2. The method for preparing a high-gloss glazed tile according to claim 1, characterized in that: The preset weight ratio in S1 is specifically 17-35% of sodium silicate, 5-8% of zinc oxide, 20-25% of calcium carbonate, 25-30% of kaolin, and 15-20% of feldspar powder.

3. The method for preparing a high-gloss glazed tile according to claim 1, characterized in that: The S2 specifically includes: S21: firstly putting the mixed raw materials in S1 into a ball mill, and then adding water into the ball mill to form an initial slurry, and controlling the weight ratio of the mixed raw materials to water to be 1:0.6 to 1:1.2; S22: ball milling the initial slurry in a ball mill, wherein the ball milling time is within 4-8 hours and the rotation speed of the ball mill is controlled at 60-120 rpm; S23: After the ball milling is completed, the slurry is filtered using a filter screen with a pore size of 0.5 microns to screen out the slurry with a particle size less than 0.5 microns for use.

4. The method for preparing a high-gloss glazed tile according to claim 1, characterized in that: The S4 specifically includes: S41: transferring the slurry containing the organic binder to a spray drying device; S42: During the spray drying process, the nozzle pressure is controlled to be 2-5 bar, and the inlet temperature of the spray drying chamber is set to be 150-200° C. and the outlet temperature is set to be 70-100° C.; S43: After drying is completed, the moisture content of the collected dry powder is controlled to be less than 0.5%.

5. The method for preparing a high-gloss glazed tile according to claim 1, characterized in that: The S5 specifically includes: S51: filling the dry powder obtained in S4 evenly into a pressing mold; S52: During the pressing process, the pressure of the press is set to 2000-5000 tons, and the pressing time is controlled to 30-60 seconds; S53: After the pressing is completed, the pressure is slowly unloaded, and the ceramic tile body is taken out of the mold at room temperature to obtain the ceramic tile body.

6. The method for preparing high-gloss glazed ceramic tiles according to claim 1, characterized in that: The S7 specifically includes: S71: placing the glazed ceramic tile body in a sintering kiln, and setting the initial temperature of the sintering kiln to room temperature; S72: gradually increasing the temperature of the sintering kiln at a rate of 100° C. per hour until the sintering temperature reaches 1250-1350° C.; S73: Maintain at the sintering temperature of S72 for 1-2 hours; S74: After the sintering process is completed, the sintering kiln temperature is gradually reduced, still at a cooling rate of 100° C. per hour; S75: After the temperature of the ceramic tile drops to room temperature, the ceramic tile is taken out from the sintering kiln to obtain the final ceramic tile product with high gloss glaze.

Citation Information

Patent Citations

  • Preparation method of reinforced bone china and product prepared therefrom

    CN103833329A